Exploring brain health knowledge and practices in young adults in Cuba: DatasetMendeley Data - Yunier Broche-Pérez; Diego D. Díaz-Guerra; Marena de la C. Hernández-Lugo; Zoylen Fernández-Fleites; Carlos Ramos-Galarza (Data in Brief)
Understanding brain health is crucial, particularly in the context of emerging public health challenges. In this scenario, this dataset aims to provide insights into Cuban youth's perceptions and awareness of brain health. The database includes information from 1, 049 Cuban participants aged between 18 and 45 years. The database is the result of a cross-sectional study conducted online, between June 30 and December 12, 2022. To explore conceptions of brain health among the Cuban population, the study utilized ``The Global Brain Health Survey''. The primary aim of this survey is to examine attitudes toward brain health and to identify factors that may encourage individuals to adopt brain health practices. By identifying knowledge gaps and misconceptions, this study highlights opportunities for improving public health initiatives tailored to this demographic. Understanding the perceptions of young people is critical, as many brain disorders develop long before clinical symptoms appear. The findings aim to inform strategies that enhance awareness and prevention efforts, ultimately contributing to better brain health outcomes among Cuban youth.